PROGRAMA UNIVERSIDADE PARA TODOS E ACESSO AO DIREITO À EDUCAÇÃO SUPERIOR : base normativa e significados na visão de beneficiári os de instituições particulares. - SALES, Iracema Melo Claudino (2019)
This research refers to the University for All Program (PROUNI), developed in the Master's D egree Program of the Graduate Program in Education, in History, Educational Policies, Work and Human Education Research Line. PROUNI is a policy focused on inclusion in higher education of low income social segments, that is, with up to three minimum wages of per capita family income, and has been under development in the country since 2004. The research questioned about the political and educational meanings of PROUNI in the inclusion of less favored segments of the population in higher education and how t he beneficiaries of this Program represent those meanings. It was defined as a general objective to analyze PROUNI's political and educational meanings, identifying contradictions, potentialities and limits in the normative basis and academic history of th e scholar. The analysis based on the historical and dialectical methodological approach, valuing the categories of totality, contradiction and mediation, in the perspective of apprehending the object, situated in a historical and social context marked by s truggles and correlation of unequal social forces. Also, bibliographic research, documentary analysis and exploratory research on the perception of PROUNI’S beneficiaries were used. In the bibliographical research, some references of specialists on the sub ject, such as Carvalho (2006, 2011 and 2015), Catani, Hey and Gilioli (2006), Chaves (2010), Germano (2005), Mancebo (2006 and 2017), Otranto (2006), Sguissardi (2006 and 2015), among others, were appreciated. In the documentary analysis normative texts (p rovisional measure, decrees and laws) and official quantitative data were included. The exploratory research on the perception of the beneficiaries was made through semi structured interviews. The results indicate that PROUNI, as a public policy focused on the confrontation of public and private interests, expresses contradictory meanings. On the one hand, the demands and struggles for access to higher education, in the expectation of emancipation and social ascension, are perceived as partly met, even wit h limits and difficulties. On the other hand, private interests (entrepreneurs of higher education) expand educational services as commodities and have the State as a partner in the maintenance of their economic privilege. In turn, the State as mediator mi nimizes the struggles for investment in public universities and meets the commitments to world capitalism.